2010
DOI: 10.1111/j.1528-1167.2010.02756.x
|View full text |Cite
|
Sign up to set email alerts
|

Human limbic encephalitis serum enhances hippocampal mossy fiber-CA3 pyramidal cell synaptic transmission

Abstract: SUMMARYPurpose: Limbic encephalitis (LE) is a central nervous system (CNS) disease characterized by subacute onset of memory loss and epileptic seizures. A well-recognized form of LE is associated with voltage-gated potassium channel complex antibodies (VGKC-Abs) in the patients' sera. We aimed to test the hypothesis that purified immunoglobulin G (IgG) from a VGKC-Ab LE serum would excite hippocampal CA3 pyramidal cells by reducing VGKC function at mossy-fiber (MF)-CA3 pyramidal cell synapses. Methods: We com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
103
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 109 publications
(114 citation statements)
references
References 38 publications
9
103
1
1
Order By: Relevance
“…Do our present findings have implications for LE with LGI1 autoimmunity? Lalic et al (29) have reported that in vitro application of serum from LE patients increased the release probability at mossy-fiber CA3 cell synapses, and this effect was mimicked by DTX. It will be interesting to determine whether the anti-LGI1 autoantibodies identified in LE patients have an impact on Kv1-channel expression.…”
Section: Discussionmentioning
confidence: 99%
“…Do our present findings have implications for LE with LGI1 autoimmunity? Lalic et al (29) have reported that in vitro application of serum from LE patients increased the release probability at mossy-fiber CA3 cell synapses, and this effect was mimicked by DTX. It will be interesting to determine whether the anti-LGI1 autoantibodies identified in LE patients have an impact on Kv1-channel expression.…”
Section: Discussionmentioning
confidence: 99%
“…Purified IgG from a patient with LGI1 increased neuronal excitability in hippocampal slices in a similar way to the snake toxin α-dendrotoxin, suggesting the antibodies act to reduce Kv1.1, 1. 2 and/or 1.6 function and are epileptogenic [54].…”
Section: Antibodies To Identified Cns Proteinsmentioning
confidence: 99%
“…As LGI1 is almost exclusively expressed in central nervous system neurons, and CASPR2 in both the central and peripheral nervous systems, the antibodies are considered likely mediators of the diseases. While careful correlations between antibody levels and clinical outcomes in individual patients, in combination with passive transfer experiments in animals, are required to formally assess VGKC-complex antibody pathogenicity, it has been proven that LGI1-antibodies can generate seizure activity in hippocampal slice cultures 16 . Interestingly, further evidence for the disease relevance of these proteins come from known genetic variations.…”
Section: The Vgkc-complex: Lgi1 Caspr2 and Contactin-2mentioning
confidence: 99%